Banjarese Muslim Figures in the Works of Karel A. Steenbrink and Martin Van Bruinessen - Mujiburrahman, Mujiburrahman (Studia Islamika, 2023)
This article analyzes the works of Dutch scholars Karel A. Steenbrink and Martin van Bruinessen, focusing on their research on Islam in Indonesia, particularly regarding the Banjarese ethnic group. Steenbrink examines Banjarese historical figures from the 18th and 19th centuries, while van Bruinessen extends the analysis to include figures from the 20th century and explores Sufi order movements such as the Sammaniya and Naqshabandiyah Orders, as well as heterodox groups. The article evaluates how these scholars presented and analyzed the roles of Muslim Banjarese figures in society through their writings and personal communications. The analysis generated both positive and negative responses from other scholars, indicating the impact and recognition of their work. Despite the Banjarese Muslims being a small part of their broader research on Islam in Indonesia, their contributions are well-regarded among scholars in the field.